Determinant of South Sulawesi Economic Growth - Aulia Rahman Bato (Jurnal Ekonomi, 2022)
This study examined the influence of consumption, exports, and investment variables on South Sulawesi's economic growth from 2010-2021. The results of the study found that consumption variables had a positive and significant effect on economic growth, as well as export variables. The high level of consumption of the community of South Sulawesi Province is strongly influenced by the per capita income, as well as the improvement of the economy of the people who rebound after the pandemic. Furthermore, the export contribution to the economy of South Sulawesi is still quite high because the export commodity in the region has a very high demand in the international market. While investment has a positive influence on the economic growth of South Sulawesi but is not significant. The investment performance in South Sulawesi began to improve as the prospect of export commodity demand was maintained, although the influence was not significant. Keywords: Consumption; Export; Investment; Economic Growth.